Manajemen Keselamatan Dan Kesehatan Kerja Dalam Mewujudkan Zero Accident - Dewi Murniati (Pusat Riset dan Inovasi Nasional, 2022)
In the industrial sector, human resources is an important asset and element that serves as a non-material capital that can be realized into physical and non physical potential in realizing the existence of the organization. Protection of occupational safety and health is often ignored, especially by those who tend to seek profit only. If a worker has an accident or a work-related illness then the agency simply replaces it with a new worker. In order to provide protection for the workforce, an agency needs to pay attention to the safety and health of the workforce by implementing Occupational Safety and Health Management.